Dry Needling with Fascial Winding in Nontraumatic Medial Tibial Shin Pain - Manoj Kumar Sharma; Sarika Chaudhary (Archives of Medicine and Health Sciences)
Shin pain is common term used to describe pain and discomfort localized on medial side of the lower leg. A significant association has been discovered between shin pain with distance runners and proving the impact of the physical demands inherent in these physical activities. Contraction of the deep leg flexors during running leads to stress transfer to the tibial fascial attachment, i.e. deep crural fascia at the medial tibial crest which results in fascial dysfunction resulting in shin pain and discomfort. Herein, we report a case of medial tibial shin pain due to fascial dysfunction in a 26-year-old male athletic who was initially treated with physical therapy, and it was failed to ease the patient’s problems completely. Dry needling with fascial winding relieved his symptoms. Dry needling with fascial winding can be a viable therapeutic option for the treatment of nontraumatic medial tibial shin pain.